TRANSLATION METHODS AND CHALLENGES OF SEWING TERMINOLOGY (American Journal of Pedagogical and Educational Research, 2025)
This article analyzes the main methods used in translating sewing (tailoring) terminology into Uzbek and the challenges encountered during this process. The study examines over 100 terms in English and Uzbek using descriptive, contrastive, empirical, and expert-based approaches. The findings indicate that methods such as direct translation, calquing, descriptive translation, transliteration, and adaptation are commonly applied. However, issues such as the absence of equivalent terms, semantic inconsistencies, and cultural differences often create difficulties. The article highlights the need for collaboration between translators and industry specialists, as well as the importance of developing specialized dictionaries. This research holds significant value for the field of professional translation, particularly in the standardization of terminology within practical vocational sectors.